Assessing The Radiopacity of Three Resin Composite Materials Using a Digital Radiography Technique - Nadhum, Noor S; Jehad, Rasha H; AbdulKareem, Shatha; Al-Hashimi, Raghad A (Journal of Baghdad College of Dentistry, 2017)
Background: Radiopacity is one of the prerequisites for dental materials, especially for composite restorations. It’s essential for easy detection of secondary dental caries as well as observation of the radiographic interface between the materials and tooth structure. The aim of this study to assess the difference in radiopacity of different resin composites using a digital x-ray system. Materials and methods: Ten specimens (6mm diameter and 1mm thickness) of three types of composite resins (Evetric, Estelite Sigma Quick,and G-aenial) were fabricated using Teflon mold. The radiopacity was assessed using dental radiography equipment in combination with a phosphor plate digital system and a grey scale value aluminum step wedge with thickness varying from 1mm to 10mm in steps of 1mm each. The tested materials were radiographed, we used Image J software, on a computer screen to evaluate the degree of radiopacity for each individual material and compare with the aluminum step wedge. Radiopacity was expressed in mm of equivalent aluminum step wedge. Analysis of varience (ANOVA) and Least Significant Difference (LSD) were used to investigate the significance of differences among the tested groups. Results: Statistical analysis showed highly significant difference among the tested groups (pâ‰¤0.01). Amongst, G-aenial composite shows the most radiopaque and it is above or equivalent to that of enamel, while Estelite Sigma Quick composite has the lowest radiopacity value and is equivalent to that of dentin. Conclusion: In line with previous studies, and within the limitation of our study, considerable variations in radiopacity values were found among materials depending on the radiopaque elements incorporated into the matrix. All composite materials tested complied with the ISO 4049 standard.